Design Of A Letter Archives Website Using Native Php In The Department Of Youth Education And Sports In Wonosobo District - Erlin Dolphina; Yani Parti Astuti; Bambang Winardi (Journal of International Multidisciplinary Research, 2024)
The Department of Education, Youth and Sports is a government agency that operates in the formal and non-formal education service sector as well as in managing education governance in schools. The Department of Education, Youth and Sports has a structural field, one of which is the SUPEG field "General and Personnel Sub-Section", where it deals with a lot of issues related to general and personnel, one of which is incoming and outgoing letters. However, there are obstacles and problems faced, namely that incoming and outgoing letters often have double numbering, some letters cannot be found, the archive process is still manual and there are many other problems. With the existence of this incoming and outgoing mail archive website, it is hoped that it will be useful and can solve this problem at SUPEG in the future. The website was designed using native PHP language and several collaboration languages, namely JavaScript, CSS and others, for the database itself using Xampp. The final result of this research is the production of an Archives Website for Incoming and Outgoing Mail. who can provide information and solve problems that occur in SUPEG "General and Personnel Sub-Section" especially in the correspondence section both within the agency and from outside.